A writer's reference - Hacker, Diana (USA : St. Martin's, 1995)
Composing and revising; Document design; Effective sentences; Word choice; Grammatical sentences; EST trouble spots; Punctuation; Spelling and mechanics; Research writing; MLA documentation; Alternative styles of documentation; Basic grammar.
Keywords: English language; English language